2022
DOI: 10.22146/ijc.76164
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Cytotoxicity Evaluation and Molecular Docking Studies of Xanthyl-Cinnamate Derivatives as Potential Anticancer Agents

Abstract: A new series of xanthyl-cinnamate hybrid compounds (4a-d) have been synthesized and screened through in vitro assay against four human cancer cell lines, i.e., HeLa, T47D, A549, and WiDr. The results revealed that xanthone hybridization with cinnamic acid increases the selectivity of the compounds with SI values of 2.75–209.03 compared to its parent oxygenated-xanthone. Compound 1,3-dihydroxyxanthen-6-yl cinnamate (4c) showed high cytotoxic activity against WiDr cell lines with an IC50 value of 39.57 µM. Molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Molecular hybridization of chalcone with other structures, such as benzimidazole and carbazole, as well as molecular hybridization of xanthone with pyran, cinnamate, and acridone carboxamides, have been reported. It was found that the hybrid compounds gave stronger anticancer and antiproliferative activities than the individual structures, revealing a synergistic effect on molecular hybridization due to multiple non-covalent interactions that could be made with the cancer cells' receptors [35][36][37][38][39]. In light of the above findings, a molecular hybridization of xanthone and chalcone could yield novel anticancer agents to be developed in the future.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Molecular hybridization of chalcone with other structures, such as benzimidazole and carbazole, as well as molecular hybridization of xanthone with pyran, cinnamate, and acridone carboxamides, have been reported. It was found that the hybrid compounds gave stronger anticancer and antiproliferative activities than the individual structures, revealing a synergistic effect on molecular hybridization due to multiple non-covalent interactions that could be made with the cancer cells' receptors [35][36][37][38][39]. In light of the above findings, a molecular hybridization of xanthone and chalcone could yield novel anticancer agents to be developed in the future.…”
Section: ■ Introductionmentioning
confidence: 93%
“…Their chemical structures are shown in Figure 1(a). However, the isolation of natural xanthones is laborious work as the isolation yield sometimes does not exceed 0.1% [20].…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22].Either 1,3,6,7-tetrahydroxyxanthone (IC 50 = 23.7 μM) or 1,3,6,8-tetrahydroxyxanthone (IC 50 = 9.18 μM) or 1,3,4,5,6-pentahydroxyxanthone (IC 50 = 12.6 μM) exhibit stronger anticancer activity than xanthone with no hydroxyl group (IC 50 = 85.3 μM), 1hydroxyxanthone (IC 50 = 43.2 μM), 3hydroxyxanthone (IC 50 = 85.3 μM), 1,3dihydroxyxanthone (IC 50 = 71.4 μM), and 1,3,6trihydroxyxanthone (IC 50 = 45.9 μM). The 1,3,6,7tetrahydroxyxanthone (IC 50 = 23.7 μM) gave weaker anticancer activity against HepG2 cancer cell line than 1,3,6,8-tetrahydroxyxanthone (IC 50 = 9.18 μM) due to the presence of 7-hydroxyl which was inactive as aforementioned above.…”
mentioning
confidence: 99%